2019
DOI: 10.1055/s-0039-1684002
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Mobile Application to Guide Health Care Professionals in Conducting Substance Use Screening and Intervention: A Mixed-Methods User Experience Study

Abstract: Mobile devices and health applications (apps), often referred to as mobile health (mHealth) products, are popular for accessing health information and providing a wide range of health services across medical disciplines and treatment settings. 1 mHealth apps can assist with patient management and monitoring, clinical decision support, and information Keywords AbstractBackground Well-documented barriers have limited the widespread, sustained adoption of screening and intervention for substance use problems in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Participants were also administered the 10-item System Usability Scale (SUS) [14] as a quantitative measure of perceived PROCare usability (scores can range from 0 to 100 with >68 considered above-average). The SUS is a valid and reliable measure commonly used for global assessments of systems usability to evaluate a wide variety of products (mobile apps, software, websites, etc), including studies evaluating patient-and provider-facing mobile apps in addiction treatment settings [15][16][17][18][19]. The SUS can be accessed online [20].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were also administered the 10-item System Usability Scale (SUS) [14] as a quantitative measure of perceived PROCare usability (scores can range from 0 to 100 with >68 considered above-average). The SUS is a valid and reliable measure commonly used for global assessments of systems usability to evaluate a wide variety of products (mobile apps, software, websites, etc), including studies evaluating patient-and provider-facing mobile apps in addiction treatment settings [15][16][17][18][19]. The SUS can be accessed online [20].…”
Section: Methodsmentioning
confidence: 99%
“…Mobile apps [105,113] [17,29,69,70,81,87,91,99,118,119,126,129,33,130,132,142, 34,36,37,49,50,53,67] [ 10,11,92,96,98,[123][124][125][50][51][52]55,61,66,72,84] [ 13,15,47,54,[56][57][58]63,75,85,108,110,23,[115][116][117]121,122,127,131,[25][26][27]30,35,40,41] Fig. 2 Relative weighting of HF/E outcomes by domain [1].…”
Section: Customized Data Displaysmentioning
confidence: 99%
“…Other unique models are being tested, including computerized referral from the ED (Haskins et al, 2017) and primary care-facilitated linkage to web-based SBIRT for patients to access after, rather than during, the medical visit (Anderson et al, 2016;Wallace et al, 2017). Moreover, computer-guided, clinician-facing products have recently been developed to help health care practitioners incorporate SBIRT skills more easily into clinical practice, including mobile device applications and clinician dashboards (Levesque, Umanzor, & de Aguiar, 2018;O'Grady, Kapoor, Gilmer, et al, 2019;Satre, Ly, Wamsley, Curtis, & Satterfield, 2017).…”
Section: Technology-based Sbirtmentioning
confidence: 99%
“…One important factor is the setting in which SBIRT is being implemented. Research has suggested that the demands of SBIRT programs in ED and primary care settings may differ on the patient as well as the site level (O'Grady, Kapoor, Kwon, et al, 2019). Even less is known about implementation needs in other settings.…”
Section: Sbirt Implementationmentioning
confidence: 99%